A Genome-First Approach to Rare Variants in Dominant Postlingual Hearing Loss Genes in a Large Adult Population. (April 2022) - Ahmadmehrabi, Shadi; Li, Binglan; Hui, Daniel; Park, Joseph; Ritchie, Marylyn; Rader, Daniel J.; Ruckenstein, Michael J.; Epstein, Douglas J.; Brant, Jason
Objective: To investigate the importance of rare variants in adult-onset hearing loss. Study Design: Genomic association study. Setting: Large biobank from tertiary care center. Methods: We investigated rare variants (minor allele frequency <5%) in 42 autosomal dominant (DFNA) postlingual hearing loss (HL) genes in 16, 657 unselected individuals in the Penn Medicine Biobank. We determined the prevalence of known pathogenic and predicted deleterious variants in subjects with audiometric-proven sensorineural hearing loss. We scanned across known postlingual DFNA HL genes to determine those most significantly contributing to the phenotype. We replicated findings in an independent cohort (UK Biobank). Results: While rare individually, when considering the accumulation of variants in all postlingual DFNA genes, more than 90% of participants carried at least 1 rare variant. Rare variants predicted to be deleterious were enriched in adults with audiometric-proven hearing loss (pure-tone average >25 dB; P = .015). Patients with a rare predicted deleterious variant had an odds ratio of 1.27 for HL compared with genotypic controls ( P = .029). Gene burden in DIABLO, PTPRQ, TJP2, and POU4F3 were independently associated with sensorineural hearing loss. Conclusion: Although prior reports have focused on common variants, we find that rare predicted deleterious variants in DFNA postlingual HL genes are enriched in patients with adult-onset HL in a large health care system population. We show the value of investigating rare variants to uncover hearing loss phenotypes related to implicated genes.